2013
DOI: 10.1186/1472-6882-13-33
|View full text |Cite
|
Sign up to set email alerts
|

A potential anti-tumor herbal medicine, Corilagin, inhibits ovarian cancer cell growth through blocking the TGF-β signaling pathways

Abstract: BackgroundPhyllanthus niruri L. is a well-known hepatoprotective and antiviral medicinal herb. Recently, we identified Corilagin as a major active component with anti-tumor activity in this herbal medicine. Corilagin is a member of the tannin family that has been discovered in many medicinal plants and has been used as an anti-inflammatory agent. However, there have been few reports of the anti-tumor effects of Corilagin, and its anti-tumor mechanism has not been investigated clearly. The aim of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 27 publications
2
84
2
3
Order By: Relevance
“…The present study further identified that corilagin is a major active component from P. niruri L. extracts and has broadspectrum antitumor activity, a better antitumor potential but lower toxicity to normal cells (12). It is effective in retarding the growth of hepatocarcinoma cells by inducing G2/M phase arrest (9); inhibiting ovarian cancer cells via TGF-β/AKT/ERK signaling pathways (10); and suppressing cholangiocarcinoma progression through the Notch signaling pathway (11). Recently, we found that corilagin enhances the sensitizing effects of chemotherapy drugs in ovarian cancer cells, through Snail epithelial-mesenchymal transition (EMT) and glycolysis pathways.…”
Section: Introductionmentioning
confidence: 86%
“…The present study further identified that corilagin is a major active component from P. niruri L. extracts and has broadspectrum antitumor activity, a better antitumor potential but lower toxicity to normal cells (12). It is effective in retarding the growth of hepatocarcinoma cells by inducing G2/M phase arrest (9); inhibiting ovarian cancer cells via TGF-β/AKT/ERK signaling pathways (10); and suppressing cholangiocarcinoma progression through the Notch signaling pathway (11). Recently, we found that corilagin enhances the sensitizing effects of chemotherapy drugs in ovarian cancer cells, through Snail epithelial-mesenchymal transition (EMT) and glycolysis pathways.…”
Section: Introductionmentioning
confidence: 86%
“…Flavonoids have demonstrated antiproliferative activity in prostate, renal, colon, non-Hodgkin's lymphoma, gastric carcinomas and neuroblastoma cancer cells [41][42][43]. Tannin isolated from Cuphea hyssopifolia, Phyllanthus niruri and Cistus ladanifer among other medicinal plants has been documented to have antiproliferative effects against breast, human promyelocytic leukemia HL-60, ovarian and pancreatic cancer cell lines [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…A tannin compound, Cuphiin D1 (CD1), isolated from Cuphea hyssopifolia has been proven to exert antiproliferative effects against human promyelocytic leukemia HL-60 cell line [31]. Corilagin, a tannin compound, isolated from a number of medicinal plants including Phyllanthus niruri has been shown to have antiproliferative effects against ovarian cancer cell lines [32]. Pancreatic cancer cells and breast cancer cells proliferation has been inhibited by Ellitannin compound isolated from the Cistus ladanifer [33].…”
Section: Discussionmentioning
confidence: 99%